Kajian Pertumbuhan A. mangium Willd pada Beberapa Famili Tanah (Studi Kasus di PT. Riau Andalan Pulp and Paper (RAPP) Riau) - , AGUS SUBECHI, S.Hut, Prof. Dr. Ir. Mohammad Naiem, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Forest management with intensive silviculture which includes selection of species, environmental manipulation, and integrated pest management essential in order to sustainable production. Right direction have been made in forest management by PT RAPP by mapping the soil up to the soil family level around the concession. The study was conducted at four family land that is HPTâFI (Hapluduluts fine), KDTâFI (Kandiudult fine), KDTâFL (Kandiudult fine loamy) and KHTâFI (Kanhapludults fine) at 1, 2 and 3 years old, that aims to determine the effect of physical and chemical soil properties on plant growth A.mangium. Highest growth response in A. mangium aged 2-3 years obtained from soil family HPT-FI by textured clay, soil with high clay texture have better fertility. Others soil family KHT-FI textured sandy loam and both soil families KDT-FI and KDT âFL textured clay loam had lower fertility than the HPT-FI. Chemical properties that affect on growth is total bases and P available, chemical properties contain the best are soil family HPT-FI, KHT-FI, KDT-FI and KDT-FL respectively. Improvement of physical properties can be done with repair and maintain humus (colloid) content and increase CEC soil which also repair chemical properties, other improvements soil chemical properties made by liming which aims to improve soil alkaline content and soil pH so nutrient of P becomes available for plants.